PUBLIC RELATION MEDIA IN AUGMENTED REALITY OF UNSEEN MUANG-LOEI ATTRACTIONS WITH BIRD EYE VIEW VIA DRONE TECHNOLOGY - Yothapakdee, Kriengsak; Sributtha, Kritsana (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Public Relation Media in Augmented Reality of Unseen Muang-LOEI Attractions with Bird’s-eye view via Unmanned Aerial Vehicle Technology, aims to study and development of public relations media for tourist destinations based on knowledge in the field of high-angle still photography with unmanned aircraft technology to create 3D models using Agisoft PhotoScan Professional software and using these models to develop public relations media in augmented reality format through Unity 3D and Vuforia software. The evaluation results of the media usage were measured by three experts and three official staff from the Loei Tourism and Sports Bureau, the efficiency average result is 4.54, the effectiveness score is 4.55, the flexibility score is 4.62, all at the highest level, the learning ability is 4.44 at a high level. And finally for user satisfaction, were evaluated by 30 tourists, have an average score at 4.52 which also at the highest level. Accordingly to the evaluation, it can be concluded that these augmented reality media are another suitable way to publicize the unseen tourist attractions in Loei province.